Superhydrophobic Cellulose Paper‐Based Triboelectric Nanogenerator for Water Drop Energy Harvesting. Issue 9 (29th July 2020) - Nie, Shuangxi; Guo, Hengyu; Lu, Yanxu; Zhuo, Jingting; Mo, Jilong; Wang, Zhong Lin
Abstract: The high‐efficiency conversion of water drop mechanical energy into electrical energy has always been an urgent issue in the development and utilization of raindrop energy. In this work, a novel drum‐like triboelectric nanogenerator (D‐TENG) with robust self‐cleaning superhydrophobic features is developed to harvest water drop energy. An elastic superhydrophobic cellulose paper is created by spray‐coating nanofumed silica dispersed in a thermoplastic elastomer solution, followed by treatment with triethoxy‐1 H, 1 H, 2 H, 2 H ‐tridecafluoro‐ n ‐octylsilane. When raindrops hit the D‐TENG surface, the superhydrophobic cellulose paper will vibrate and periodic contact and separation with polytetrafluoroethylene will occur to generate electricity. The results demonstrate that when a 6 mm water drop falls from a height of 2.5 m and hits the D‐TENG, the generated voltage output can reach a peak of 21.6 V and charge transfer of 10 nC. The output power of the D‐TENG can reach 16 µW per droplet, which is more than 13.3 times that generated from the previous TENGs based on the electrostatic induction of water droplets. These results indicate that the superhydrophobic cellulose paper‐based D‐TENG is potentially a strong candidate for harvesting energy from raindrops, thereby making it a promising sustainable energy source for next‐generation electronics. Abstract : A novel drum‐like triboelectric nanogenerator (D‐TENG) with robust self‐cleaning superhydrophobic features is developed to harvest water drop energy. The output power of this D‐TENG can reach 16 µW per droplet, which is 13.3 times more than that generated from the previous TENGs based on the electrostatic induction of water droplets.